2006
DOI: 10.1002/app.24256
|View full text |Cite
|
Sign up to set email alerts
|

Modification of polyacrylonitrile precursors for carbon fiber via copolymerization of acrylonitrile with ammonium itaconate

Abstract: Ammonium-modified polyacrylonitrile was prepared by free-radical solution copolymerization of acrylonitrile (AN) with ammonium itaconate (AIA), and then it was spun into precursor fibers in this study. Effects of AIA and itaconic acid on the characteristics of the copolymers and precursor fibers were studied in contrast. It has been found that the ammonium modification could obviously increase the hydrophilicity of the copolymer. And in the spinning processes, modified copolymer can withstand higher total draw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 9 publications
0
8
1
Order By: Relevance
“…The experimental conditions and characteristics of the synthesized polymers are summarized in Table 1. It was noteworthy that the PAN copolymers containing CA synthesized in this study showed higher M v than those synthesized in earlier reports using other comonomers such as methyl acrylate (MA) and IA [11,12], suggesting that the presence of CA comonomer accelerated the growth of polymer chains, leading to higher molecular weight. So far, the large diameter of the polymer fibers has been one of the limitations of carbon fiber strength.…”
Section: Resultscontrasting
confidence: 45%
“…The experimental conditions and characteristics of the synthesized polymers are summarized in Table 1. It was noteworthy that the PAN copolymers containing CA synthesized in this study showed higher M v than those synthesized in earlier reports using other comonomers such as methyl acrylate (MA) and IA [11,12], suggesting that the presence of CA comonomer accelerated the growth of polymer chains, leading to higher molecular weight. So far, the large diameter of the polymer fibers has been one of the limitations of carbon fiber strength.…”
Section: Resultscontrasting
confidence: 45%
“…Comonomers incorpo rated into the polymer chain destroy its regularity; change the degree of crystallinity of PAN, the rheolog CN ical characteristics of its solutions, and the tensile strength of fibers; promote widening and shifting of the temperature range of PAN cyclization and oxida tion; etc. The magnitude of these changes is deter mined by not only the chemical nature of a comono mer but also its content in the chain [2][3][4][5][6][7][8][9][10]. Thus, additives of itaconic acid, acrylic acid, and meth acrylic acid promote a shift of the cyclization reaction onset toward lower temperatures than that for the AN homopolymer [2][3][4][5], while the presence of methy lacrylate units in the chain has the opposite effect [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of these changes is deter mined by not only the chemical nature of a comono mer but also its content in the chain [2][3][4][5][6][7][8][9][10]. Thus, additives of itaconic acid, acrylic acid, and meth acrylic acid promote a shift of the cyclization reaction onset toward lower temperatures than that for the AN homopolymer [2][3][4][5], while the presence of methy lacrylate units in the chain has the opposite effect [6,7]. If acrylamide is used as a comonomer, the temper ature range of the cyclization reaction is determined by its content, i.e., the copolymer composition [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Solution and aqueous suspension are the most common useful techniques. [3][4][5] The solvent-water suspension method is a new and promising technique. It cleverly combines the advantages of solution and those of aqueous suspension.…”
Section: Introductionmentioning
confidence: 99%